Revisiting nation branding: An infrastructure financing perspective in Zimbabwe - Farai Chigora; Tonderai Kapesa; Paul Svongoro (International Journal of Financial, Accounting, and Management, 2021)
Purpose: This study aimed to reconfigure nation branding theories and concepts through infrastructure financing intervention. Research methodology: Data were collected using a QUAL to QUAN sequential mixed methods. Results: Qualitative research informed that the infrastructure that is required for nation branding to be road networks; airports; Information Communication Technologies (ICTs); reliable power supply; industrial facilities; tourism facilities; healthcare facilities; educational facilities; educational facilities; and residential accommodation. These were then classified into two, namely, economic and social infrastructure. Results from quantitative research showed that there is a positive relationship between nation branding and infrastructure financing. Also, it showed that road infrastructure and airports were the most related to nation branding with public-private partnerships and bilateral/multilateral loans to finance their development, respectively. Limitations: As a result of the COVID-19, the research did not manage to have some focus groups for a depth understanding and comprehensive response of the participants. Contribution: The results will help the Zimbabwean government consider developing the road networks and airports to enhance the nation’s brand.